Pengaruh Variasi Umpan Buatan Pancing Tonda (Trolling) terhadap Hasil Tangkap Ikan Tengiri di Perairan Desa Sedayulawas Kecamatan Brondong Kabupaten Lamongan - Muhammad Rizal Cahyono; Achmad Kusyairi; Alif Astagia (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2025)
Bait is an important factor in luring fish to hook on the hook. The aim is to find out the effect of the differences between artificial bait and natural bait for mackerel on mackerel fish catches and to find out which bait is more optimal for mackerel fish catches. The method used in this research is the Experimental Fishing method by making direct observations of the treatments tried when operating trolling equipment with artificial bait that resembles fish, then making direct observations of the number of mackerel fish caught and conducting direct interviews with fishermen. The results of the analysis based on the T test results on the artificial and natural bait treatments can be concluded that the two-sided p value is greater than 0.05, so the results do not reject the null hypothesis. This means there is no significant difference between the two types of artificial bait and natural flowerfish bait. Then, to determine the success of the catch in both treatments, a hook rate test was carried out. The total number of catches during the research for fishing rods using artificial bait had a hook rate of 56.25% and fishing rods using natural bait had a hook rate of 37.5%. From the catches, it can be seen that those who use artificial bait that resembles fish have a higher catch or hook rate than those who use natural mackerel bait.kan umpan ikan tenggiri alami.